(untitled) (Journal of the College of Basic Education, 2022)
The aim of the research is to enumerate classroom (methodological) and non-descriptive sports activities as competitions between classes, and to know the effect of sports activity on aggressive behavior among a sample of middle school students, and to know the effect of classroom and extracurricular sports activity on some components of physical fitness among middle school students. The experimental approach (with The one group) being more appropriate with the research problem, as the sample was chosen from (89) students from the second grade average in the justice medium in the third Karkh educationAfter 8 weeks, post-tests were conducted, and the results of the data were statistically processed. After presentation and discussion, results were reached that the physical education lesson has a direct impact on reducing aggressive behavior among second-grade students. Also, the physical education lesson has a direct impact on some components of physical fitness as it appeared. Significant differences with statistical significance in the proportion of aggressive behavior and in favor of the post test. There were significant statistically significant differences in the physical fitness tests and in favor of the post tests.